2016
DOI: 10.1684/epd.2016.0792
|View full text |Cite
|
Sign up to set email alerts
|

A case of recurrent status epilepticus and successful management with progesterone

Abstract: Catamenial epilepsy (CE) is a commonly observed phenomenon among women with epilepsy, the management of which is both hormonal and non‐hormonal. Progesterone therapy has been tried in these patients, as the possible mechanism of CE is withdrawal of progesterone and a higher oestrogen/progesterone ratio in the perimenstrual and periovulatory periods. Here, we describe a 24‐year‐old lady with multiple seizure types since childhood, which were refractory to adequate antiepileptic drug therapy after menarche with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Few neurosteroids, including allopregnanolone, tetrahydrodeoxycorticosterone, and 3-alpha androstanediol, are inhibitory neurosteroids, meaning that they augment GABAergic signaling [17]. Only allopregnanolone showed in vitro and in vivo e cacy in controlling seizures in women with catamenial epilepsy as well as adult and pediatric RSE patients [9,10,13]. Our results show concordant ndings with other previous animal and human studies demonstrating that allopregnanolone improves control of seizures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Few neurosteroids, including allopregnanolone, tetrahydrodeoxycorticosterone, and 3-alpha androstanediol, are inhibitory neurosteroids, meaning that they augment GABAergic signaling [17]. Only allopregnanolone showed in vitro and in vivo e cacy in controlling seizures in women with catamenial epilepsy as well as adult and pediatric RSE patients [9,10,13]. Our results show concordant ndings with other previous animal and human studies demonstrating that allopregnanolone improves control of seizures.…”
Section: Discussionsupporting
confidence: 90%
“…Allopregnanolone, a reduced progesterone metabolite and a positive allosteric modulator of γaminobutyric acid type A (GABA A ) receptor-mediated conduction, can reduce neuronal excitabilities and increase seizure thresholds, thus yielding a reduction of epileptiform discharges [7,8]. Previous clinical studies showed that both oral and parenteral forms of progesterone can improve seizure control as well as suppress seizure discharges in electroencephalography (EEG) [9,10]. These studies indicate that progesterone contains antiepileptic properties.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a successful treatment of SE in a woman with recurrent SE episodes was also reported (Ramanujam et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Intravenous progesterone for critically ill and injured patients has been demonstrated safe and inexpensive (Wigginton et al 2010). Recently, a successful treatment of SE in a woman with recurrent SE episodes was also reported (Ramanujam et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In one of these, 14 women with refractory partial seizures and normal ovulatory cycles were given parenteral depomedroxyprogesterone at 120-150 mg every 6-12 weeks, and had 39% seizure reduction. However, it is unclear whether the effect was due to direct anticonvulsant activity of medroxyprogesterone or to the hormonal consequences of the induced amenorrhea [15][16][17][18] .…”
Section: Articlementioning
confidence: 99%